Analysis of Water Prices in Urban Systems: Experience from Three Basins in Southern Portugal - Roseta-Palma, C.; Monteiro, H.; Coutinho, P. B.; Fernandes, P. A. (8.º Congresso Ibérico de Gestão e Planeamento da Água, 2013)
The economic analysis of water uses is one of the main components of river basin management plans (RBMP), as established by the Water Framework Directive. Thus the RBMP for the Portuguese river basin districts (RBD) 6 – Sado/Mira, 7 – Guadiana and 8 – Ribeiras do Algarve included a thorough economic analysis of urban drinking water supply (WS) and wastewater drainage and treatment (WWDT) systems. This paper summarizes results on the role of prices, encompassing the assessment of cost-recovery levels, the discussion of current tariff structures, the estimation of residential water demand elasticities and an appraisal of affordability conditions. RBD7 has the lowest cost-recovery levels, namely in WWDT, but revenue is insufficient to guarantee financial equilibrium in all RBD. As for current tariff structures, they are far from complying with the economic regulator’s recommendations or meeting economic efficiency criteria. The estimated residential water demand elasticities indicate that climate change may have a strong impact on demanded quantity, whereas price has a significant but limited impact on moderating demand, illustrating the need for a combination of price and non-price policies. On the other hand, low price elasticities imply that price increases could be effective in writing off current tariff deficits. Average household expenses with water services are still substantially lower than the OECD recommended threshold, although tariff increases need to be done in a way that ensures access to the poorer households.